Kurier Mazowsza . wiadomości Grup Oporu "Solidarni" RKW NSZZ "S[olidarność]" Mazowsze, no. 47, 1989 - [ed. in cooperation with Biuro Informacji NSZZ "Solidarność" Region Mazowsze and Grupy Oporu "Solidarni" (Grupy Oporu "Solidarni", 1989)
Creation and circulation: From issue no. 72(1989) published legally; In 1989 published in two formats 15 and 30 cm. The 30 cm edition with singlesided print was designed for noticeboards.